(untitled) (Research, Society and Development, 2024)
Research aim: evaluate, under the perspective of the caregivers, the health care services provided to children in early childhood in Porto Velho – RO, considering the essential and derived attributes of Primary Health Care children’s version. Method: transversal, quantitative study, carried out with 190 family members or caregivers responsible for children from zero to five years old, all being followed-up in a basic health unit from Porto Velho – RO, in 2021. The Primary Care Assessment Tool was used with definition (≥ 6,6) or low (< 6,6) orientation for Primary Health Care. Results: as the caregivers evaluated, there was a high guidance from the service to Primary Health Care, with general score (6,80) and essential score (7,27). Conclusion: the study revealed attributes with satisfactory scores, which reflects positive aspects of the evaluated health service. However, it is considered essential to rethink and intervene on factors that proved to be unsatisfactory for the quality of the Primary Health Care service for children.